Josephson Plasmon Resonance in Tl2Ba2CaCu2O8 High‐Temperature Superconductor Tunable Terahertz Metamaterials. (23rd September 2021) - Guo, Rong; Duan, Siyu; He, Ze; Liang, Xuelian; Niu, Zihan; He, Ming; Jiang, Yushun; Wu, Jingbo; Ji, Lu; Jin, Biaobing; Chen, Jian; Wang, Huabing; et al.
Abstract: The Josephson plasmon resonance (JPR) offers a valuable probe to investigate the superconductivity in layered cuprate superconductors. However, the coupling between free space radiation and JPR in high‐temperature superconductor (HTS) film remains challenging because the excitation of JPR demands the c ‐axis oriented electric field. The subwavelength resonators in metamaterials can enhance the localized electric field, which can be utilized to resolve this difficulty. Here, a tunable terahertz (THz) metamaterial made from Tl2 Ba2 CaCu2 O8 (Tl‐2212) HTS film is developed. The spectral response of Tl‐2212 metamaterial has a tunable property at temperatures up to 90 K. The resonant excitation of Josephson plasmon in the metamaterial is observed. Simulation results indicate that the scattering of subwavelength resonators can provide the component of the z ‐axis electric field for the resonant excitation. The coupling between JPR and resonance modes of metamaterials is observed and explained using coupled mode theory. The temperature dependence of JPR frequency shows accordance with the experimental results of the pure film. This work provides an avenue to excite the JPR and probe superconducting condensate in the layered superconductor. The development of Josephson plasmonic metamaterials may contribute to tunable and nonlinear THz devices. Abstract : Josephson plasmon resonance (JPR) is observed in high temperature superconductor Tl‐2212 metamaterial. This metamaterial offers an intriguing way to couple the JPR with free space radiation and probe the superconducting carriers in the layered superconductor. With the introduction of Josephson plasmons into metamaterials, the tuning and nonlinear properties can be exploited to develop various functional devices.